Correlation between vegetative dysfunction and cognitive impairment in patients with chronic ischemia of the brain - T. V. Mokina; D. A. Doschannikov; Ye. A. Аntipenko; A. V. Gustov (Бюллетень сибирской медицины, 2008)
The purpose of present research is to estimate the correlation between vegetative dysfunction and cognitive impairment in patients with chronic ischemia of the brain. We supervised 112 patients with chronic ischemia of the brain. To determine cognitive impairment we used Mini Mental State Examination scale. To determine vegetative dysfunction we used A.M.Vayne's questionnaire. Also heart rate variability (HRV) examination was carried out. All the patients were divided into 2 groups depending on expressiveness of cognitive impairment: light and moderate cognitive impairment. The expressed vegetative dysfunction was revealed according to A.M.Vejna's questionnaire and according to HRV in patients with moderate cognitive impairment. In patients with chronic ischemia of the brain with moderate cognitive impairment revealed shift of vegetative balance aside prevalence of hyperactivity of sympathetic adrenal system that is adverse the factor in progressing a chronic ischemia of a brain.